Kepemimpinan dan Budaya Organisasi Dalam Meningkatkan Kinerja Karyawan - Amal, Muhammad Khairul (Cantaka: Jurnal Ilmu Ekonomi dan Manajemen, 2023)
Leadership and organizational culture are important factors that determine employee performance and ability to adapt to environmental changes. The phenomenon that occurs at the PT Olindo is the work of employees who are still not optimal. The problem studied in this study is how the leadership and organizational culture of PT Olindo is portrayed. This study aims to determine and describe the influence of leadership and organizational culture on the work of employees of the PT Olindo, both simultaneously and partially. Data from this study are all employees of PT Olindo totaling 95 people. The sampling technique in this study uses population census techniques so that the entire population is used as a sample. The data collection questionnaire method is used, and multiple regression analysis with simultaneous testing and partial test hypothesis testing is the analysis method used in this investigation. According to partial variable results from regression analysis, leadership, and organizational culture have a beneficial impact on employee performance. Leadership, the dominant independent variable, affects employee performance by 69.3%. The magnitude of the influence of the independent variable on the bond is 75.0% while the remaining 25. 0% is influenced by other factors not studied such as salary and performance support. This research discusses theories about human resources and contributes to expanding the literature on leadership, organizational culture, and employee performance from an organizational context.